Residual resistance of impact-damaged reinforced concrete beams - Adhikary, Satadru Das (2015)
The behaviour of reinforced concrete (RC) beams under single or repetitive drop-weight impact loading has come under increasing attention within the engineering community in the past decades. However, until now, little effort has been sought towards examining the residual resistance of RC beams after impact damage. To contribute towards a better understanding in this area, both experimental and numerical investigations were carried out. The beams were first tested under drop-weight impact loading. Subsequently, quasi-static bending tests were conducted on the same specimens to obtain the residual behaviour. Thereafter, one beam from each series without any prior damage was tested under monotonic static loading to compare its behaviour with impact-damaged specimens. Furthermore, to investigate the structural response in detail, a numerical procedure was developed in an explicit finite-element program. Upon successful validation of the numerical results with the experimental outcomes, numerical case studies were carried out to quantify the variation of residual resistance index in terms of various parameters.